IRMS as a tool to obtain the carbon turnover (δ13C) in organs of weaned piglets fed glutamic acid and nucleotides. Issue 3 (29th March 2019) - Anton Dib Saleh, Mayra; Sousa dos Santos, Luan; Antonio Berto, Dirlei; Borges Amorim, Alessandro; Lívio Panhoza Tse, Marcos; Eliodoro Costa, Vladimir
Abstract: Early weaning of piglets causes stress characterized by a decrease in feed intake followed by a decline in growth rates; thus, a fast recovery represents an essential step for proper growth of these animals. Considering that IRMS is a potential tool for non‐destructive sampling and the fact that it provides time‐integrated estimate of assimilated and not just ingested nutrients turned possible its application to evaluate the effects of dietary nucleotides and glutamate on carbon turnover (δ 13 C) in organs of weanling piglets. At day 0, three piglets were slaughtered (prior to diet switch), the remaining eighty‐four piglets weaned at 21‐day‐old were randomly assigned in a complete block design with a 2 × 2 factorial arrangement of treatments (two Nu levels: 0 and 0.1% and two Glu levels: 0 and 1%), being three piglets per treatment slaughtered on trial days 3, 6, 9, 14, 21, 35 and 49. The samples were analysed by IRMS and adjusted to first‐order equation by a non‐linear regression analysis using NLIN of SAS, in order to establish exponential graphics. After that, the turnover data were submitted to analysis of variance using GLM of SAS. The turnover value (t95% ) verified for spleen was faster ( p < 0.05) when glutamate was supplemented in diets. For pancreas and liver, the turnover rates were faster ( p < 0.05) for the mixture of additives. However, for renal tissue, the turnover rate (t95% ) was greater ( p < 0.05) for the free additive diet. The results obtained suggest that the mixture of additives was more efficient to develop the digestive tract at post‐weaning phase, taking into account the functional importance of pancreas and liver for nutrients' digestion and processing.